PENGARUH KEAKTIFAN BERORGANISASI, LINGKUNGAN TEMAN SEBAYA, DAN PERILAKU BELAJAR TERHADAP PRESTASI AKADEMIK MAHASISWA AKUNTANSI UNIVERSITAS SLAMET RIYADI SURAKARTA - Ady Nugroho, Djoko Kristianto & Suharno (Jurnal Akuntansi dan Sistem Teknologi Informasi, 2016)
The purpose of this research is to know about the siginificant influence of being active in organization, friend zone and study behavior through accounting students academic effort of Slamet Riyadi University Surakarta. The population of this research is student of accounting periode 2012, 2013, and 2014. Followed the student organization in Slamet Riyadi University Surakarta. This research give to 59 responden. Base on the result of the research test using double linear regression test showed: (1) Being active in organization have positive influence and not significant to academic effort students of accounting in Slamet Riyadi University of Surakarta.Its showed from the statistic point 0,008 with p value 0,994 > 0,05, and coefisien of positive regression (0,001). (2) The friends zone have positive influence and not significant to academic effort students of accounting Slamet Riyadi University of Surakarta. Its look from statistic point t 0,068 with p value 0,545 > 0,05, and coefficient positive regression (0,547). (3) Study behavior have positive influence and significant to academic effort students of accounting Slamet Riyadi University of Surakarta. Its showed from the statistic point t 7,904 with p value 0,000< 0,05, and coefficient positive regression (0,547) so if study behavior level up so academic effort students of accounting Slamet Riyadi of Surakrta will be level up. (4) Being active in organization, friends zone and study behavior together influenced to academic effort students of accounting Slamet Riyadi University of Surakarta. Its showed from the point of F 20,828 with p value 0,000 < 0,05Keyword: being active in organization, the friends zone, study behavior, academic effort